10 years after the fall of the Wall : public opinion in Central and East European countries in transition, 1989-1999 / prepared by Dina Smeltz, Janice Bell, Nancy Mendrala, Anna Sweeney, Mark Teare. - Smeltz, Dina. (Tufts University. Tisch Library., 2019)
1 online resource (167 pages) : illustrations (some color)